2012
DOI: 10.1007/s10750-012-1135-8
|View full text |Cite
|
Sign up to set email alerts
|

Young-of-the-year fish assemblages as indicators of anthropogenic disturbances in large tributaries of the Seine River Basin (France)

Abstract: A variety of indices targeting a number of different biological assemblages have been developed to assess aquatic ecosystem condition, identify the drivers of alteration and provide information on possible restoration measures. Fish-based indices, commonly focused on adult assemblages, are capable of indicating declines in condition, but often provide limited information on the ultimate causes for the observed changes. Using young-of-the-year (YOY) fish assemblages has been suggested as a means of improving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Because many characteristics of the flow regime influence the structure and functioning of river ecosystems (Schlosser 1991;Poff et al 1997;Humphries et al 1999;Magoulick and Kobza 2003), an improved understanding of the ecological effects of hydropeaking is needed. This is particularly true for fish assemblages, which can be affected by hydropeaking at several levels: increased drift of individuals during rapid flow velocity increases (Lechner et al 2016), stranding due to rapid shoreline dewatering (Leclere et al 2012;Hauer et al 2014;Sauterleute et al 2016), and repeated drying and scouring of spawning grounds (McMichael et al 2005;Malcolm et al 2012;Casas-Mulet et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Because many characteristics of the flow regime influence the structure and functioning of river ecosystems (Schlosser 1991;Poff et al 1997;Humphries et al 1999;Magoulick and Kobza 2003), an improved understanding of the ecological effects of hydropeaking is needed. This is particularly true for fish assemblages, which can be affected by hydropeaking at several levels: increased drift of individuals during rapid flow velocity increases (Lechner et al 2016), stranding due to rapid shoreline dewatering (Leclere et al 2012;Hauer et al 2014;Sauterleute et al 2016), and repeated drying and scouring of spawning grounds (McMichael et al 2005;Malcolm et al 2012;Casas-Mulet et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, navigation intensity provides a significant pressure on fish assemblages of large rivers, which moreover interacts with the hydromorphological degradation of the river channel. Surprisingly, inland navigation has not been considered in analyzes of multiple pressures so far, except the study by Leclere et al (2012). The authors modeled occurrence of fish species based on environmental parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The authors modeled occurrence of fish species based on environmental parameters. They reported that inland navigation and physico-chemical disturbances both negatively influence the occurrence of juveniles of selected fish species (Leclere et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Fishes are useful indicators of environmental disturbances in lowland rivers because the various guilds integrate a wide range of conditions over their life cycles that are linked to the habitat requirements of particular species and ontogenetic stages (Copp, ; Schiemer, ; Welcomme, Winemiller, & Cowx, ). Larvae and 0+ juveniles are particularly applicable in this respect because tolerable habitat conditions are often much narrower for such fishes compared with older and larger individuals, owing to the strict physical and energetic constraints facing young fishes (Schiemer, Spindler, Wintersberger, Schneider, & Chovanec, ; Schiemer, Flore, & Keckeis, ; Flore, Keckeis, & Schiemer, ; Jurajda, Slavík, White, & Adámek, ; Leclere, Belliard, & Oberdorff, ; Musil, Horký, Slavík, Zbořil, & Horká, ). Morphological and behavioral limitations often restrict the early developmental stages of fishes to specific habitats, which, together with their small size and fragility, means that larval and 0+ juvenile fishes are more susceptible than adults to adverse changes in their environment (Copp, Olivier, Peňáz, & Roux, ; Schiemer & Waidbacher, ; Sogard, ; Jones & Petreman, ).…”
Section: Introductionmentioning
confidence: 99%